Processo de produção de etanol de segunda geração (E2G) - Santos, Murilo dos (Universidade Federal de São Carlos, 2025)
Second-generation ethanol (2G Ethanol), also known as bioethanol, green ethanol, or cellulosic ethanol, is an advanced biofuel made from the residual materials left over from the production of conventional ethanol (first-generation ethanol) and sugar. It is a product that utilizes raw materials with low environmental impact that would otherwise be discarded, offering excellent logistical advantages. Chemically, second-generation ethanol (2G Ethanol) is the same as first-generation ethanol (1G); the main difference lies in the production method, which uses plant biomass, repurposing agricultural residues such as straw, leaves, bagasse, wood chips, and others. The production of second-generation ethanol involves a highly technological process including biomass pretreatment, hydrolysis, and subsequent fermentation. Among the advantages of this production process are: the utilization of residues such as sugarcane bagasse and straw, corn leftovers, wheat straw, and more, which would normally be discarded or burned. This contributes to the circular economy by transforming waste into renewable energy, promoting efficient use of resources, and reducing waste. The process also yields a higher output per hectare, meaning more ethanol is produced per cultivated area without the need to expand plantations, which helps preserve forests and other ecosystems. It strengthens a clean and renewable energy matrix and reduces dependence on fossil fuels. Finally, it contributes to the reduction of greenhouse gas emissions, as its production emits up to 90% less CO₂ compared to fossil fuels, and even less than first-generation ethanol. Currently, this production process is considered high-cost because the conversion of cellulose and hemicellulose into fermentable sugars is technically complex and requires the use of enzymes or thermochemical processes that are still expensive. Despite technological advances, the conversion efficiency is still lower than that of first-generation ethanol, which affects production profitability. However, looking at future prospects, costs are expected to decrease as the technology matures and scales up, in addition to benefits from tax incentives and the growing demand for cleaner fuels. The production of 2G Ethanol can be crucial for countries aiming to meet decarbonization targets and achieve a greener energy transition. In summary, second-generation ethanol is considered a promising solution to global energy challenges, promoting more efficient use of biomass and reinforcing Brazil’s role as a global leader in biofuel production.
Second-generation ethanol (E2G) production process
Keywords: Etanol E2G; Resíduos; Impacto Ambiental; 2G Ethanol; Residues; Environmental Impact; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA